Public Revenue Risk Management in Central Governments: A Systematic Literature Review - Siregar, Oktarini Khamilah; Napitupulu, Juni Yanti; Buaya, Register Launli; Apriliani, Sundari (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study presents a systematic review of recent academic literature on public risk management in central government settings, with a specific focus on the revenue sector. Using the PRISMA-guided Systematic Literature Review (SLR) approach, it analyzes 30 peer-reviewed articles published between 2019 and 2024. The selected articles were classified based on research methods, theoretical frameworks, country contexts, and revenue-related risk phenomena. The findings reveal that the implementation of risk management in central governments remains limited, fragmented, and often symbolic. Risk management practices are not yet fully integrated into strategic decision-making. Key challenges include rigid bureaucratic systems, institutional pressures, and organizational cultures that lack strong risk awareness. Additionally, there is a clear gap between theoretical frameworks and practical application. The study highlights the need for future research to adopt multidisciplinary approaches that align more closely with institutional realities and evolving fiscal challenges. Such research should aim to bridge the gap between theory and practice and offer more adaptive, context-specific strategies for managing public revenue risks. From a practical perspective, this review provides useful insights for policymakers and practitioners in developing risk management systems that go beyond administrative compliance. It promotes the use of risk management as a strategic tool to strengthen fiscal resilience and institutional legitimacy. The study offers original value by combining quantitative and qualitative analyses to build a reflective framework for improving risk governance. It supports a more contextual, participatory, and public value–oriented approach to managing risks in the revenue sector of central governments.